Tipe Love pada Individu yang Berpacaran Long Distance Relationship dan Proximal Relationship di Bandung - Fiona Christie; Cindy Maria (Humanitas (Jurnal Psikologi), 2020)
This study aims to test the presence of different types of love that is reviewed from the love components (intimacy, passion, and commitment) in emerging adult who are going through the courtship long distance relationship (LDR) and proximal relationship (PR). The study used quantitative approach and involving 200 subjects, consisting of 100 subjects who are undergoing a LDR and 100 subjects who are undergoing a PR. The questionnaire is a modification of Sternberg's Triangle Love Scale (STLS). Based on data, obtained significance value of 0.754. The conclusion is no difference in love types owned by emerging adult who is having a longdistance relationship and proximal relationship. Based on data, it is known that the intimacy component has significance value of 0.002, passion of 0.05, and commitment of 0.001 so there is a bonding between components of love and gender. Intimacy has a significance value of 0.027 and commitment of 0.004 which means there is a bonding between the passion and intimacy with the number of dating experiences. Keywords: love type, intimacy, passion, commitment